Islamic Family Law Reform in Indonesia Through Supreme Court Circulars: A Maqasid Sharia Perspective - Arrasyid, Fauzan; Pagar, Pagar; Tanjung, Dhiauddin (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2023)
From 2012 to 2022, the Supreme Court of the Republic of Indonesia has issued ten new regulations through Supreme Court Circulars (SEMA) resulting from Plenary Chamber Meetings, which have produced 458 new legal rules. Among these new legal rules, 109 govern Islamic civil law, indicating that SEMAs represent another variation in the efforts to reform Islamic family law in Indonesia. This research aims to examine the existence and efforts of Islamic family law reform in Indonesia from the perspective of maqasid sharia according to contemporary scholars. This research uses a mixed-method approach, employing both statutory and conceptual approaches. Primary data sources consist of SEMAs from 2012 to 2022, and secondary data consist of legal regulations related to issues of Islamic family law, which are analyzed. The theory used for data analysis is the theory of maqasid sharia. The results of this research show that the reform of Islamic family law regulations in Indonesia through SEMAs from 2012 to 2022 is integrative with maqasid sharia. The regulations issued in SEMAs have fulfilled six aspects of maqasid sharia, namely: (a) aspects of faith, creed, and monotheism; (b) aspects of human nature and moral improvement; (c) aspects of common sense and legal contextualization; (d) aspects of human rights, freedom, equality, justice, and women's rights; (e) aspects of good order and civilization; (f) aspects of public interest (maslahah)